The other side of the rainbow; with Judy Garland on the dawn patrol. - Tormé, Mel, 1925-1999 (W. Morrow, 1970)
"The Judy Garland Show," which aired Sunday nights at nine on CBS twenty-six times between June 1963 and March 1964, was the last glimmer of a fading star. As Dorothy in The Wizard of Oz Judy Garland had charmed the world, singing and dancing down a golden path to fame; now she was middle-aged and wracked with personal problems, habitually late for rehearsals, often not showing up at all. In The Other Side of the Rainbow, Mel Torme takes us on a Hollywood roller-coaster ride through the triumphs and disasters of this short-lived show, at the same time revealing a personal side of Judy Garland rarely glimpsed.